Experiences of Classroom Techniques and Learning Outcomes - Metsärinne, Mika; Kallio, Manne (Design and Technology Education: An International Journal, 2014)
This article is a part of a research project that is aimed to explore how the background variables of learning are related to learning outcomes in a Sloyd subject, internationally referred to as Craft, Design and Technology. The research question of this article is: “How are ninth grade pupils’ experiences of classroom techniques related to their learning outcomes?” The empirical data is based on an evaluation by the Finnish National Board of Education (FNBE). The data (n = 4,792) was collected by stratified sampling from 152 schools. The data of pupils’ experiences of classroom techniques was gathered in a specified questionnaire using a narrowed sample (n = 1,548). Three main orientations for learning were found: Learner-Centred Learning, Teacher-Directed Learning and Collaborative Learning. Furthermore, two orientations were formed of technical and textile technology areas of the subject.Analysis revealed that participating in either classes of technical technology area or textile-technology area predicted success in the other area as well. Thus, learning outcomes in one area correlate with the learning outcomes in the other. Due to this result, the effects of learning orientations were analyzed separately for both technology areas. Experiences of Learner-Centred Learning predicted success in technical technology area while experiences of Teacher-Directed Learning predicted success in textile technology area. Collaborative Learning didn’t predict success in either of the areas. The results can be applied in developing the subject more towards the learners’ point of view.